Hybrid renewable/grid power systems, an essential for base transceiver station penetration in Rural Nigeria - Ebiega, Godslove I.; Dugeri, Terdoo M.; Irefu, Ovis D. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The energy crisis in Nigeria has continued to impede the rapid expansion of the telecommunication industry, whose operating expenditure is galloping due to over-dependence on diesel generators as an alternative source of power to its base transceiver station (BTS). This fossil-fuel power source has also increased the industry’s carbon footprint. As a solution to these problems, the objective of this work is to provide a sustainable and quality hybrid DC power supply system for BTS that would increase access to information and communication technology or ICT infrastructure. This involves the integration of solar & wind energy with the grid. The sizing of the hybrid sub-systems was designed & simulated using MATLAB Simulink to test for functionality. A prototype of the design system was then implemented with the results showing an average power output that guarantees 21 hours/day of supply. By installing this hybrid system of 1.3 kW, approximately 2.55 kg of diesel (C10H20) would be un-utilized by one BTS, thereby preventing 3.6 kg of CO2 from been emitted to the atmosphere daily. Extrapolating these values shows 930.75 kg of diesel can be saved and reduce 1314 kg of CO2 emission within a year. Hence eliminating the need for diesel-backup generator for a grid connected or non-grid BTS sited in rural areas.